Immune Interactions during the Reproductive Cycle - Stavros Giaglis (Frontiers Research Topics, 2015)
Mammalian pregnancy represents a unique immunological riddle in that the mother does not reject her allogeneic fetus. In part this is largely due to a general sequestration or diminution of T cell activity, and an increased involvement of the innate immune system. The field of immunology is concerned primarily with how innate and adaptive mechanisms collaborate to protect vertebrates from infection. Although many cellular and molecular actors have evidently important roles, antibodies and lymphocytes are considered to be the principal players. Yet despite their importance, it would be definitely simplistic to conclude that they are solely essential for immunity overall. A major distinction between adaptive and innate immunity is the spontaneity of the innate immune response, which utilizes an already pre-existing but limited repertoire of responding modules. The slower onset of adaptive immunity compensates by its ability to recognize a much broader repertory of foreign substances, and also by its power to constantly improve during a response, whereas innate immunity remains relatively unaffected. The interactions between the reproductive system and the immune system are of particular interest, since the reproductive system is unique in that its primary role is to assure the continuity of the species, while the immune system provides internal protection and thus facilitates continued health and survival. The modus operandi of these two morphologically diffuse systems involves widely distributed chemical signals in response to environmental input, and both systems must interact for the normal functioning of each. Furthermore, dysregulation of normal physiological interactions between the reproductive and immune systems can lead to severe pregnancy-related disorders or complications. On the other hand, by ameliorating auto-inflammatory conditions such as MS and RA, pregnancy may provide a unique insight into novel immune modulatory strategies. The scientific focus on reproductive-immune research has historically provided substantial insight into the interface between these two physiological systems. A translational research approach would involve a tight interaction between diverse scientific and clinical disciplines including immunology, obstetrics, haematology, haemostasis and endocrinology. With so much recent progress in the field, we believe that it is valuable and well-timed to review the broad variety of the relevant physiologic and pathologic aspects - from menstruation to fertilization and implantation, and from placentation and pregnancy per se to the post partum condition - in which the immune system takes part. We are looking forward to a wide and vivid discussion of these and related issues, and we sincerely expect that our readers profoundly benefit from new exciting insights and fruitful collaborations.